2016
DOI: 10.1016/j.alit.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of central nervous system histamine receptors in psychological stress-induced exacerbation of allergic airway inflammation in mice

Abstract: These results suggest that H1R, but not H3/4R, may be involved in stress-induced asthma exacerbations in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The proportions of collagen fibers in peribronchial regions were evaluated by Masson’s trichrome staining. The number of eosinophils and PAS-positive cells were calculated in each of the 5 random bronchioles in 3 lung sections from each mouse [26].…”
Section: Methodsmentioning
confidence: 99%
“…The proportions of collagen fibers in peribronchial regions were evaluated by Masson’s trichrome staining. The number of eosinophils and PAS-positive cells were calculated in each of the 5 random bronchioles in 3 lung sections from each mouse [26].…”
Section: Methodsmentioning
confidence: 99%
“…Miyasaka et al. injected histamine receptor (H1R and H2R) antagonists into the brain ventricles of stressed asthmatic mice and discovered a significant reduction in peripheral airway inflammation, and eosinophil and lymphocyte infiltrations were considerably lowered, which indicated that allergens under stress may increase the severity of the inflammatory response to asthma by stimulating the release of histamine to activate histamine receptors (H1R and H2R) in the brain region ( 49 ). Consequently, the regulation of the expression of these neurotransmitter molecules can be used as an effective means to manage asthma symptoms.…”
Section: Asthma and Neuro-immune-mediated “Lung–brain” Crosstalkmentioning
confidence: 99%
“…In addition to the above information, acute restraint stress itself is affected by the histaminergic system working in the brain 7 Histamine. plays a dual role as an inhibitory and excitatory neurotransmitter, which is frequently relevant to psychological stress 8 . The importance of histamine neurons in controlling many behavioral responses such as the state of being awake has been shown as well as stress.…”
Section: Introductionmentioning
confidence: 99%
“…7 Histamine plays a dual role as an inhibitory and excitatory neurotransmitter, which is frequently relevant to psychological stress. 8 The importance of histamine neurons in controlling many behavioral responses such as the state of being awake has been shown as well as stress. Hence, long-term block of the histaminergic system will have significant effects on behavioral and physiological challenges and of course, different body reaction to physical stress is one of them.…”
Section: Introductionmentioning
confidence: 99%